Genetically determined angiotensin converting enzyme level and myocardial tolerance to ischemia - Messadi, Erij (Federation of American Societies for Experimental Biology, 2010)
Angiotensin I-converting enzyme (ACE; kininase II) levels in humans are genetically determined. ACE levels have been linked to risk of myocardial infarction, but the association has been inconsistent, and the causality underlying it remains undocumented. We tested the hypothesis that genetic variation in ACE levels influences myocardial tolerance to ischemia. We studied ischemia-reperfusion injury in mice bearing 1 (ACE1c), 2 (ACE2c, wild type), or 3 (ACE3c) functional copies of the ACE gene and displaying an ACE level range similar to humans. Infarct size in ACE1c was 29% lower than in ACE2c (P<0.05). Pretreatment with a kinin B2 receptor antagonist suppressed this reduction. In ACE3c, infarct size was the same as in ACE2c. But ischemic preconditioning, which reduced infarct size in ACE2c (−63%, P<0.001) and ACE1c (−52%, P<0.05), was not efficient in ACE3c (−2%, NS, P<0.01 vs. ACE2c). In ACE3c, ischemic preconditioning did not decrease myocardial inflammation or cardiomyocyte apoptosis. Pretreatment with a renin inhibitor had no cardioprotective effect in ACE2c, but in ACE3c partially restored (38%) the cardioprotection of ischemic preconditioning. Thus, a modest genetic increase in ACE impairs myocardial tolerance to ischemia. ACE level plays a critical role in cardiac ischemia, through both kinin and angiotensin mediated mechanisms.—Messadi, E., Vincent, M.-P., Griol-Charhbili, V., Mandet, C., Colucci, J., Krege, J. H., Bruneval, P., Bouby, N., Smithies, O., Alhenc-Gelas, F., Richer, C. Genetically determined angiotensin converting enzyme level and myocardial tolerance to ischemia.